The promises and perils of the neuroscience of creativity - Abraham, Anna (Frontiers in Human Neuroscience, 2013)
Our ability to think creatively is one of the factors that make our lives exciting as it introduces novelty and opens up new possibilities which in turn lead to developments in a host of fields from science and technology to art and culture. While research on the influence of biologically-based factors on creativity has a long history, the advent of modern techniques for investigating brain structure and function in the past two decades have resulted in an exponential increase in the number of neuroscientific studies that have explored creativity. The field of creative neurocognition is a rapidly growing area of research that can appear chaotic and inaccessible because of the heterogeneity associated with the creativity construct and the many approaches through which it can be examined. There are also significant methodological and conceptual problems that are specific to the neuroscientific study of creativity that pose considerable limitations on our capacity to make true advances in understanding the brain basis of creativity. This article explore three key issues that need to be addressed so that barriers in the way of relevant progress being made within the field can be avoided. a) Are creativity neuroimaging paradigms optimal enough? b) What makes creative cognition different from normative cognition? c) Do we need to distinguish between types of creativity?